Legality of Ownership Rights through Land Certificates issued by the Village Head - Mutia Dewi , Rury; Farma Rahayu, Mella Ismelina (Journal of Law, Politic and Humanities, 2024)
This article is entitled, Legality of Property Rights through Land Information issued by the Village Head, using a normative research type and using secondary data as analysis material. The results of the analysis are land ownership rights in the UUPA as proof of ownership, namely a certificate. However, the village head's SKT can be used as a historical guide in registering land to obtain a certificate at the land office, on the basis of physical and written evidence with coherent research on land ownership and supporting written evidence. This decision is based on Indonesia using a negative publication system that has a positive tendency. So the Village Head's Land Certificate can only be used as written evidence to register for labor, but the village head's SKT is not proof of recognized land ownership rights.